Predicting of psychological well-being with adoloscents according to personality traits and life goals: Ergenlerde psikolojik iyi oluşun kişilik özellikleri ve yaşam amaçları değişkenlerine göre yordanması - Çelik, Seda; Cihangir Çankaya, Zeynep (Journal of Human Sciences, 2022)
This study was conducted in order to determine the predictive power of relationships with personality traits and life goals in psychological well-being of adolescents. Psychological Well-being Scale, Life Goals Scale, Adjective Based Personality Scale and Personal İnformation Form were used in the study to collect the data. In the first part of the research, The validity and realibity studies of Psychological Well-being Scale, Life Goals Scale, Adjective Based Personality Scale was conducted with 635 adoloscents. The second part of the research data were collected from 933 adolescents to determine predictive power of relationships with intrinsic-extrinsic life goals, openness to experience, conscientious, extroversion, aggreableness, neuroticisim on the psychological well-being of adolescents. Stepwise multiple regression analysis was used in the process of data analysis. The results of the analysis showed that intrinsic-extrinsic life goals, openness to experience, conscientious, extroversion, aggreableness, neuroticisim scores significantly predicted the psychological well-being of adolescents and explained 47.6 % of change in their psychological well-being. These findings were discussed in the light of the relevant literature and developmental features of adolescents. ​Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Bu araştırma ergenlerin psikolojik iyi oluş düzeylerinin, kişilik özellikleri ve yaşam amaçları değişkenleri açısından yordanma gücünün belirlenmesi amacı ile gerçekleştirilmiştir. Araştırmada veri toplama aracı olarak Psikolojik İyi Olma Ölçekleri, Yaşam Amaçları Ölçeği, Sıfatlara Dayalı Kişilik Testi, Kişisel Bilgi Formu kullanılmıştır. Araştırmanın birinci kısmında Psikolojik İyi Olma Ölçekleri, Yaşam Amaçları ve Sıfatlara Dayalı Kişilik Testi’nin geçerlik ve güvenirlik çalışmaları 635 ergen ile gerçekleştirilmiştir. Araştırmanın ikinci kısmında ergenlerin psikolojik iyi oluş düzeylerinin, içsel ve dışsal yaşam amaçları, dışa dönüklük, nevrotizm, sorumluluk, deneyime açıklık, yumuşak başlılık, duygusal dengesizlik, değişkenleri açısından yordanma gücünün belirlenmesi amacıyla 933 ergenden veri toplanmıştır. Verilerin analizinde aşamalı çoklu regresyon analizi kullanılmıştır. Yapılan analiz sonrasında içsel ve dışsal yaşam amaçları, dışa dönüklük, nevrotizm, sorumluluk, deneyime açıklık, yumuşak başlılık, duygusal dengesizlik değişkenlerinin ergenlerin psikolojik iyi oluş düzeylerini anlamlı bir biçimde yordadığı ve birlikte ergenlerin psikolojik iyi oluşundaki değişimin % 47.6’sını açıkladığı bulunmuştur. Araştırma bulguları, ilgili araştırmalar ve ergenlerin gelişimsel özellikleri çerçevesinde tartışılmıştır.